Understanding offender managers’ views and experiences of psychological consultations - Blinkhorn, Victoria (European journal of probation, 2021)
Few studies have investigated the effectiveness of the psychological consultation process specifically for offender managers. This study involves a total of 23 offender managers’ views and perceptions of the consultation process within four areas of the North West of England. Within each location, a focus group was conducted involving between four and eight participants and interpretative phenomenological analysis was used to analyse the responses. The analysis revealed four main themes: validation of thoughts, feelings and practice; professional support; a personal touch; and room for improvement. These findings are discussed along with implications for further research.